MENINGKATKAN MINAT PEMBELIAN DAN INOVASI BARU DARI FISHOTEL MAKANAN KHAS DAERAH BESUKI - Sildalina Tri Octavia; Febri Ariyantiningsih; Firdauzy Amalia; Nur Afifa (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
Fishotel is a Besuki specialty made from fish that has great potential as a local culinary product based on local wisdom. However, its existence faces challenges in the form of changing consumption patterns and competition with modern foods. This discussion aims to analyze consumer purchasing interest and the role of product innovation in increasing Fishotel's competitiveness. The method used is a qualitative descriptive approach through a literature review and product condition analysis. The results of the discussion indicate that Fishotel purchasing interest is influenced by the quality of raw materials, taste, price, packaging, and marketing strategy. Product innovations such as the addition of chili oil, variations in accompanying spices, and the use of vacuum packaging have been proven to increase the added value and appeal of the product without losing its traditional identity. With the right innovation and marketing strategies, Fishotel has the potential to develop into a superior regional product while supporting the preservation of traditional Besuki culinary.